Influence of additional static stresses on biaxial low-cycle fatigue of 2024 aluminum alloy (Fracture and Structural Integrity, 2022)
In this paper, a previously developed modification of the Sainz model of multiaxial fatigue is reduced to an invariant form. Model constants were determined for different sets of setup experiments. It was supposed to introduce an additional summand to account for the phase shift between loading modes. The model is used to describe the fatigue behavior of the D16T aluminum alloy. Low-cycle fatigue tests under biaxial loading conditions are presented, with one mode changing cyclically and the other mode remaining constant in magnitude throughout the test. The results of cyclic durability prediction by the modified model provide good convergence.
Keywords: Low-cycle fatigue; Aluminum alloy; Сomplex stress state; Fatigue life; Experimental research